2015
DOI: 10.1111/jbi.12512
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of climate warming on populations of silver fir (Abies alba) across Europe

Abstract: 28Climate change can modify mid to long term forest growth across a tree 29 biogeographical range. In the Mediterranean basin, the predicted increase in aridity is 30 expected to cause growth decline for several temperate tree species that are in the rear-31 edge (southernmost limit) of their distribution area. Empirical evidence suggests that the 32 forecasted growth decline seems to be site-and species-specific, but few studies have 33 considered the response of a species along its entire distribution range.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
106
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 54 publications
19
106
0
3
Order By: Relevance
“…The increased share of silver fir in the upper layer was more pronounced in basal area than in stem density and it was the consequence of gradual height transfers of silver fir from the middle layer. In the case of a more obvious increase in basal area, it was likely supported also by the increased radial growth of silver fir that was recently reported in studies from several European regions [16,24,61]. Although, in NNR Dobročský prales, the site conditions represent the optimum for silver fir (large number of seedlings, increase in basal area and growing stock), individuals of natural regeneration of this tree species did not exceed 20 cm in height and their development was limited, most likely due to the ungulate browsing (personal observation) and competition of common beech.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The increased share of silver fir in the upper layer was more pronounced in basal area than in stem density and it was the consequence of gradual height transfers of silver fir from the middle layer. In the case of a more obvious increase in basal area, it was likely supported also by the increased radial growth of silver fir that was recently reported in studies from several European regions [16,24,61]. Although, in NNR Dobročský prales, the site conditions represent the optimum for silver fir (large number of seedlings, increase in basal area and growing stock), individuals of natural regeneration of this tree species did not exceed 20 cm in height and their development was limited, most likely due to the ungulate browsing (personal observation) and competition of common beech.…”
Section: Discussionsupporting
confidence: 59%
“…On the contrary, many authors make reference to the increasing dominance of common beech observed in forests across Europe [7,13,14]. Responses to natural and anthropogenic disturbances in mixed stands are usually very complicated and each tree species can respond to similar disturbances with different intensities [15,16]. The dynamic of natural mixed forests is driven by disturbances of smaller scale and higher frequency, that remove single or eventually small groups of trees and favour multi-layered stand structure, but also by less frequent disturbances of intermediate or large scale, that allow shade-intolerant species to establish and survive [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The raw tree-ring width series of three age-classes of trees were detrended by the negative exponential curve or by linear regression, and the standard chronologies (STD), the residual chronology (RES) and the arstan chronology (ARS) removing non-climatic growth effects were subsequently developed utilizing the ARSTAN program [31]. The tree-ring width chronology containing more high-frequency signals is better in assessing climate-growth relationships [32]. Given the above, we selected the residual chronology for the analysis of the radial growth responses of different age-class trees to climate change.…”
Section: Field Sampling Tree Age-class Divisions and Tree-ring Chronmentioning
confidence: 99%
“…The standard chronology is more suited for the long-term trend analysis, which retains more low-frequency (mainly decade or more) growth variability (Dang et al 2013). By contrast, the residual chronology by removing the problem of biological persistence in the resulting series using autoregressive modeling, contains more high-frequency signals (mainly annual), which is better in assessing climate-growth relationships (Sánchez-Salguero et al 2010;Jiang et al 2014;Gazol et al 2015). In addition, the residual chronology avoids possible 'end-effect' bias due to index inflation after calculating ratios and dose not offset the formerly temperature sensitive with less low-frequency trend, which is suitable for analyzing 'divergence problem' (He et al 2014;Schneider et al 2014).…”
Section: Tree-ring Materials and Statistical Analysesmentioning
confidence: 99%